1997
DOI: 10.1093/oxfordjournals.jbchem.a021880
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Organization of the OS-9 Gene Amplified in Human Sarcomas

Abstract: The OS-9 gene is frequently amplified in human sarcomas. We isolated and characterized an OS-9 genomic DNA from a human BAC library. Sequencing of the genomic DNA showed that the gene spanned approximately 30.4 kbp and had 15 exons. The 1,010 bp sequence of the 5' upstream region was also determined. The potential binding-sequence motifs TATA and CCAAT for general transcription factors were found in the 5' upstream region. Primer extension analysis revealed two putative transcription start sites. The significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…In addition, we found that such splicing can occur also in the rat tissues, despite the fact that all 10 rat OS-9 clones (including OS-9/L1) obtained from the two-hybrid library screening, corresponded to the non-spliced variant (homologous to the isoform 1 of hOS-9). The splicing event identified in the rat and the mouse OS-9 isoforms occurs at exactly the same position (corresponding to exon 13), as in hOS-9 (16,26), suggesting that the OS-9 gene in all three species might have a conserved exon/intron organization in this region.…”
Section: Identification Of the Region In The Cytoplasmic Tail Of Meprmentioning
confidence: 84%
“…In addition, we found that such splicing can occur also in the rat tissues, despite the fact that all 10 rat OS-9 clones (including OS-9/L1) obtained from the two-hybrid library screening, corresponded to the non-spliced variant (homologous to the isoform 1 of hOS-9). The splicing event identified in the rat and the mouse OS-9 isoforms occurs at exactly the same position (corresponding to exon 13), as in hOS-9 (16,26), suggesting that the OS-9 gene in all three species might have a conserved exon/intron organization in this region.…”
Section: Identification Of the Region In The Cytoplasmic Tail Of Meprmentioning
confidence: 84%
“…The putative risk gene OS9 consists of 15 exons and encodes four different splice variants [45,46], all of which contain a mannose 6-phosphate receptor homology domain [47]. The OS9 protein plays an important role in the ER-associated degradation of misfolded or unassembled proteins [48,49].…”
Section: Discussionmentioning
confidence: 99%
“…Cells-The OS-9 gene is composed of 15 exons (17). Alternative splicing events that conform to the GT-AG rule could generate 4 variants of the protein.…”
Section: Two Splice Variants Of Os-9 Are Expressed In Mammalianmentioning
confidence: 99%